2013
DOI: 10.1017/s0967199413000038
|View full text |Cite
|
Sign up to set email alerts
|

A role for polyglucans in a model sea urchin embryo cellular interaction

Abstract: The enzymatic activities of commercially prepared glycosidases were verified by direct chemical assays using defined substrates and fixed and live sea urchin (Lytechinus pictus) embryos to determine if a model cellular interaction of interest to developmental biologists for over a century (interaction of archenteron tip and roof of the blastocoel) was mediated by glycans. Glycosidases (active and denatured) were incubated with microdissected archenterons and blastocoel roofs in a direct assay to learn if their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Then we assess whether or not the gut will attach to the blastocoel roof in the presence or absence of independently characterized contaminant-free glycosidases. In this way we are able to provide convincing evidence for a role of specific glycans in mediating a specific model cellular interaction in a model system [3]. In these experiments, using independently characterized glycosidases, we have found a role for polyglucans in this cellular interaction.…”
Section: Microdissection Assaysupporting
confidence: 54%
See 2 more Smart Citations
“…Then we assess whether or not the gut will attach to the blastocoel roof in the presence or absence of independently characterized contaminant-free glycosidases. In this way we are able to provide convincing evidence for a role of specific glycans in mediating a specific model cellular interaction in a model system [3]. In these experiments, using independently characterized glycosidases, we have found a role for polyglucans in this cellular interaction.…”
Section: Microdissection Assaysupporting
confidence: 54%
“…Because of its transparency and simplicity, the sea urchin is well suited for research in glycobiology. We have developed new assays using the sea urchin embryo to learn about the roles of specific glycans in mediating cellular interactions [2][3][4][5]. The first assay involves culturing sea urchin embryos in 96 well microplates with and without glycans or glycosidases over time and counting the different morphologies of the developing gut (archenteron) in tens of thousands of living embryos [2,4].…”
Section: The Sea Urchin Nih Designated Model System Microplate Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The most important finding is that the current assay has quantitatively been able to identify a specific sugar of interest with great statistical reliability in thousands of living, swimming embryos. The next series of experiments will involve use of α- l -rhamnosidase in similar quantitative assays and also using micro-dissected archenterons and blastocoel roofs (Singh et al ., 2013) to determine if l (–)-rhamnose is directly involved in adhesion between the archenteron and blastocoel roof. This series will help to pinpoint l (–)-rhamnose's mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of polyglucans has been identified recently as involved in mediation of the adhesive interaction between the tip of the archenteron and the blastocoel roof (Singh et al ., 2013). In the present study, the sugar l (–)-rhamnose is identified as a putative component in the control of archenteron elongation and attachment to the blastocoel roof.…”
Section: Introductionmentioning
confidence: 99%